Implementasi Konsep Cheerful Pada Interior Health and Beauty Care for Baby and Kids di Surabaya - Natalia Sugiharto (Intra, 2013)
Development of the era that followed by the change in lifestyle of modern society makes the competition in the higher areas of the business. The impact of this competition seen in the field of spa business. Beauty and health care needs that initially was limited to only requirement is now considered a lifestyle of upper class society. Not only adults but children were also able to obtain health and beauty care with full facilities from head to toe. With the interior design of the Health and Beauty Care for Baby and Kids in Surabaya infants and children are pampered with full amenities ranging from hair care, massage and swimming, as well as manicure-pedicure. This design took the theme of